Pengaruh Electronic Word Of Mouth pada Media Sosial Facebook terhadap Keputusan Berkunjung ke Desa Wisata Nglanggeran Gunungkidul - Ali Hasan; Niken Widiati Setiyaningtiyas (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2015)
The research was conducted to determine whether the decision to visit for affecting domestic or foreign tourists to visit Nglanggeran Tourism Village even by individual or together in influencing the decision to visit Nglanggeran. The research was conducted in tourist attraction Nglanggeran Tourism Village from December 2014 until January 2015. Data were obtained from questionnaires that have been given a modified Likert Scale rating to 100 tourists who visited Nglanggeran. The sampling was done by the Accidental Sampling technique. The analysis method used in this research is multiple linear regression with SPSS 16 Program for Windows. The result of this research demonstrates the value of the coefficient of determination R Square of 0.421 (42.21%) while the rest of 57.79% is influenced by other factors that are not described in this research. While the result of t (partial) demonstrate show that X4 “Helping the Company” is the most significant variable to decisions visited Nglanggeran Tourism Village. From the test result F (simultaneous) shows the result of F count 12.960 > F table 2.19. It shows that variable X1, X2, X3, X4 and X5 simultaneously positive and significant impact on the decision to visit. From the test result of T (partial) demonstrate it shows that X1 t count -1.882 < t table 1.98 and level of significance 0.063 < 0.05, it means that Concern for Others (X1) don’t affect the decision to visit. X2 t count -4.165 < t table 1.985 and level of significant 0.0000 < 0.05, it means that Expressing Positive Feelings (X2) affect negatively the decision to visit. X3 t count 6.752 > t table 1.985 and level of significant 0.000 < 0.0,5 affect the decision to visit. X4 t count 4.905 > t table 1.985 and level of significant 0.000 < 0.05it means X4 affect the decision to visit. X5 t count 0.0297 < t table 1.985 and level of significant 0.767 > 0.05, it means X5 don’t affect the decision to visit. Based on Beta Coefficient test 1.221 and t count 4.905, it shows that X4 has the strongest factor that affects the decision to visit.